Experiences of English as Foreign Language student using ICT in their learning process - Silva-Perdomo, Julian Dario; Duero-Naranjo, María Soledad; Castañeda Trujillo, Jairo Enrique (GIST – Education and Learning Research Journal, 2022)
This article presents the results of a narrative analysis that looked into some EFL students’ experiences related to their English learning processes and the use of ICT (Information and Communication Technologies). The study was carried out at a university in southern Colombia. The main objective was to understand the participants’ experiences in the institutional English courses at a university while using ICT during their language learning process. The data was collected through in-depth interviews and life stories. The English students’ experiences are relevant to validating a new teaching tool or strategy in a specific context. The main conclusion indicates that ICT in language teaching needs to be articulated with other appropriate tools, practices, methodologies, and approaches to achieve meaningful learning.